Anti‐Inflammatory/Tissue Repair Macrophages Enhance the Cartilage‐Forming Capacity of Human Bone Marrow‐Derived Mesenchymal Stromal Cells. Issue 6 (June 2015) - Sesia, Sergio B.; Duhr, Ralph; Medeiros da Cunha, Carolina; Todorov, Atanas; Schaeren, Stefan; Padovan, Elisabetta; Spagnoli, Giulio; Martin, Ivan; Barbero, Andrea
<x xml:space="preserve">Abstract</x> Macrophages are key players in healing processes. However, little is known on their capacity to modulate the differentiation potential of mesenchymal stem/stromal cells (MSC). Here we investigated whether macrophages (Mf) with, respectively, pro‐inflammatory and tissue‐remodeling traits differentially modulate chondrogenesis of bone marrow derived‐MSC (BM‐MSC). We demonstrated that coculture in collagen scaffolds of BM‐MSC with Mf derived from monocytes polarized with M‐CSF (M‐Mf), but not with GM‐CSF (GM‐Mf) resulted in significantly higher glycosaminoglycan (GAG) content than what would be expected from an equal number of BM‐MSC alone (defined as chondro‐induction). Moreover, type II collagen was expressed at significantly higher levels in BM‐MSC/M‐Mf as compared to BM‐MSC/GM‐Mf constructs, while type X collagen expression was unaffected. In order to understand the possible cellular mechanism accounting for chondro‐induction, developing monoculture and coculture tissues were digested and the properties of the isolated BM‐MSC analysed. We observed that as compared to monocultures, in coculture with M‐Mf, BM‐MSC decreased less markedly in number and exhibited higher clonogenic and chondrogenic capacity. Despite their chondro‐inductive effect in vitro, M‐Mf did not modulate the cartilage tissue maturation in subcutaneous pockets of nude mice, as evidenced by similar accumulation of type X collagen and calcified tissue. Our results demonstrate that coculture of BM‐MSC with M‐Mf results in synergistic cartilage tissue formation in vitro. Such effect seems to result from the survival of BM‐MSC with high chondrogenic capacity. Studies in an orthotopic in vivo model are necessary to assess the clinical relevance of our findings in the context of cartilage repair. J. Cell. Physiol. 230: 1258–1269, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company